TRAINING IN MAKING ORGANIC COMPOST TO BUILD THE CHARACTER OF ENVIRONMENTAL CARE IN STUDENTS OF ELEMENTARY SCHOOLS 13 TALIWANG - Haryani, Poppy; Sejati, Martina Ayu; Manalu, Tugma Jaya; Suharto, Prihutomo; Gusri, Rahmat (LPPM Univ. Ibn Khaldun Bogor, 2025)
Land productivity is significantly influenced by the patterns of land use and management practices employed. The excessive application of chemical composts and pesticides has been shown to degrade soil fertility and pose long-term threats to environmental sustainability. To mitigate these adverse effects, it is essential to introduce the principles of conservation-oriented agriculture from an early age. This community engagement activity was designed to provide elementary students at SD Negeri 13 Taliwang, West Sumbawa Regency, with direct experience in the production and application of organic compost. Moreover, the program aligns with the objectives of the Pancasila Student Profile Strengthening Project (P5), particularly through its focus on practical planting activities using potted plants. The implementation methods included an introductory session on the concept and environmental benefits of bokashi, which included a practical session involving direct student participation in the compost making process. Besides introducing eco-friendly technologies, the activity fostered environmental awareness among students. Similar programs should be continued to support early understanding of sustainable agriculture.